Application of the PRICE Method in Handling Acute Injuries and Trauma Among Karangpandan Volunteers - Sutrisno; Vitri Dyah Herawati; Fajar Alam Putra (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
Acute injuries or acute trauma often occur as a result of accidents on the road or due to other activities such as exercising or working. Acute injuries require immediate attention to avoid complications and increase the victim's comfort. One method of acute trauma relief is PRICE (protection, rest, ice, compression, elevation). Karangpandan volunteers are a self-dedicated group working independently on their own initiative to help the community. Knowledge and skills in handling injuries are important things that they must master. The implementation method is in the form of training activities on PRICE, demonstrating skills in using the PRICE method in everyday injury management. This activity involved 24 volunteers from Karangpandan Volunteers. The method of assessing knowledge and skills uses a questionnaire and checklist sheet, each containing 10 question/observation items. The results of the activity show an increase in knowledge and skills regarding the use of the PRICE method by volunteers.